The President and his inner circle : leadership style and the advisory process in foreign affairs - Preston, Thomas, 1963- (Power, conflict, and democracy., 2001)
Few would argue that presidential policies and performance would have been the same whether John F. Kennedy or Richard Nixon became president in 1960, or if Jimmy Carter instead of Ronald Reagan had won the White House in 1980. Indeed, in recent elections, the character, prior policy experience, or personalities of candidates have played an increasing role in our assessments of their ""fit"" for the Oval Office. Further, these same characteristics are often used to explain an administration's success or failure in policy making. Obviously, who the president is-and what he is like-matters